1992
DOI: 10.1021/ma00042a005
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of polyethylene in the inclusion complex with perhydrotriphenylene

Abstract: The influences of channel size and structure on the molecular dynamics of polyethylene at 300K have been studied using the inclusion complex of n;tetracontane with perhydrotriphenylene. The diameter of the channel in the real physical system is enlarged by 1 or2 A to provide alternative sizes.rhe content ofgauche (G) states rises from almost nil in the real physical channel to a value in the channel enlarged by 2 A that is nearly half of the result seen with the free unperturbed chain.The population of G*TG+ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…The last column on Table 3 shows the characteristic ratios defined as C n =〈r 2 〉/nl 2 , with n=40 skeletal bonds in this case. Our result of 4.8 for the isolated PE chain is slightly smaller than those of C ∞ experimentally obtained [22] or calculated [21] ; [23] that are in the range 5.2-7.0, although it should be taken into account that our chains are rather short and C n probably has not yet reached the asymptotic C ∞ limit.…”
Section: Conformational Analysis Of the Polymer Chainscontrasting
confidence: 88%
“…The last column on Table 3 shows the characteristic ratios defined as C n =〈r 2 〉/nl 2 , with n=40 skeletal bonds in this case. Our result of 4.8 for the isolated PE chain is slightly smaller than those of C ∞ experimentally obtained [22] or calculated [21] ; [23] that are in the range 5.2-7.0, although it should be taken into account that our chains are rather short and C n probably has not yet reached the asymptotic C ∞ limit.…”
Section: Conformational Analysis Of the Polymer Chainscontrasting
confidence: 88%
“…This result excludes diffusion type motions of the entire chains around their axes, which have been identified as primary modes in polymer dynamics in simple inclusion compounds. [23][24][25][26] The 13 C signal of PEO in the supramolecules shows only one resonance, even down to low temperature of 180 K. This experimental result exclude another possibility of conformational transitions. 27 Considering the structural constraints along the nanochannels and uniform conformation of PEO, a two-site helical jump of PEO entire chains about their axes is further investigated.…”
mentioning
confidence: 94%
“…In brief, we developed initial models by packing mesogenic dimers with an antiparallel in the molecules from one stable rotational isomer to another, may also occur on a time scale of picoseconds association into periodic boxes. Relaxed models were obtained by application of cycles of energy minimization [9,10,12].…”
Section: Simulationsmentioning
confidence: 99%
“…Further molecular dynamics studies con® rm that a polyethylene chain strongly prefers a trans conformation for the chain in perhydroruns under (NPT) conditions were performed on these relaxed models at the temperature of each smectic phase triphenylene or in urea crystals. Simulations [12] of molecular dynamics found that the transitions between [7] to obtain their equilibrated structures in the smectic phase. Fluctuations of the volumes of the systems were trans and gauche states at internal CH2± CH2 bonds of an n -alkane chain are strongly suppressed by the channel observed during the equilibration, and the deviations of the corresponding densities were 0.23% for the smectic A of perhydrotriphenylene; these transitions are only allowed near the ends of the chain when the temperature phase and 0.13% for the smectic E phase.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation